Analyzing the Effect of Infrastructure and Facility Quality on Customer Satisfaction - Eryco Muhdaliha; Setyani Dwi Lestari; Panca Maulana; Abdul Rohman (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine the effect of infrastructure, facilities, and services on customer satisfaction of Integrated Mass Rapid Transit users in a region. This study uses a descriptive survey method with data collection through questionnaires that have been tested for validity and reliability. The sample of this study involved 95 Integrated Mass Rapid Transit users spread across 13 Integrated Mass Rapid Transit stations, with a purposive sampling technique based on certain criteria such as frequency of use and travel purpose. Data analysis was conducted using SPSS and Structural Equation Modeling (SEM). The results of this study indicate that infrastructure and facilities have a significant effect on customer satisfaction, while services also contribute to increasing user satisfaction. Based on these findings, it is recommended that MRT managers continue to improve the quality of infrastructure, facilities, and services in order to increase customer satisfaction and loyalty. These findings provide an important contribution to the planning and management of more effective and sustainable public transportation, especially in supporting the development of a multimodal and integrated transportation system in the region.